Methods of linear and Lagrange interpolation to fill in 3D motion trajectory - Pędzioł, Mateusz; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2016)
During the motion registration using passive motion capture system in the marker’s trajectory a gap may appear, which in the data post-processing should be filled in. Various interpolation algorithms are used for this purpose. This article presents three different interpolation methods: linear, polynomial of Lagrange of second degree and fifth degree. In the original 3D data the holes have been created, which are then filled in by mentioned methods. Each method was evaluated by measuring the Euklides distance for three dimensions of the original and interpolated data. The article presents the program to interpolate gaps in the trajectory, implemented in C ++ language. The analysis concerns the interpolation of selected marker’s trajectory which belongs to the Plug-in Gait model while performing walking.